Refractive, Topographic, and Aberrometric Results at 2-Year Follow-Up for Accelerated Corneal Cross-Link for Progressive Keratoconus - Ercüment Bozkurt; Engin Bilge Ozgurhan; Betul Ilkay Sezgin Akcay; Tugba Kurt; Yusuf Yildirim; Zehra Karaagaç Günaydin; Ahmet Demirok (Journal of Ophthalmology, 2017)
Purpose. To report the visual, refractive, and corneal topography and wavefront aberration results of accelerated corneal cross-linking (CXL) during a 24-month follow-up. Methods. Forty-seven eyes underwent riboflavin-ultraviolet A-induced accelerated CXL treatment (30 mW/cm2 with a total dose of 7.2 joules/cm2). Uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), spherical and cylindrical values, keratometry (K) measurements (Ksteep, Kflat, Kavg, and Kapex), central corneal thickness, and anterior corneal aberrometric analyses including total wavefront error (WFE), total high order aberration (HOA), astigmatism, trefoil, coma, quadrafoil, secondary astigmatism, and spherical aberration were evaluated. Results. The mean UDVA and CDVA were significantly improved at 1 (p=0.003 and p=0.004, resp.) and 2 years after treatment (p=0.001 and p=0.001, resp.). The mean Ksteep, Kflat, Kaverage, and Kapex values were significantly lower than baseline at 12 months (p=0.008, p=0.024, p=0.001, and p=0.014, resp.) and 24 months (p=0.014, p=0.017, p=0.001, and p=0.012, resp.). Corneal thickness showed a significant decrease at 1 month. Total HOA and coma decreased significantly at the 12-month (p=0.001 and p=0.009, resp.) and 24-month visits (p=0.001 and p=0.007, resp.). Conclusion. Accelerated CXL (30 mW/cm2) was found to be effective in improving UDVA, CDVA, corneal topography readings, total HOA, and coma aberrations during the 24-month follow-up.